A study of gonadal dysfunction in women with thyroid disease - Vasudevan, Manasa Saligrama; Hosalli, Naveenkumar (International Journal of Advances in Medicine, 2022)
Background: Thyroid diseases are among the commonest endocrine disorders. It effects growth, embryonic development, tissue differentiation, maturation, metabolism, increases chronotropic and inotropic action of heart. The aim was to study gonadal dysfunction in women with thyroid disease; to study levels of FSH, LH, prolactin, estrogen and testosterone in hypothyroid and hyperthyroid. Methods: All participants fulfilling the inclusion criteria were interviewed as per proforma and medical details were recorded in proforma sheet and patients were subjected to necessary blood investigations. Results: Among 80 study subjects, majority were in the age group 26-35 years (60.1%) and majority had overt hypothyroid disease (72.5%). Symptoms of hypothyroid subjects mainly were fatigue, weight gain, hair loss, oligomenorrhea. Hyperthyroid subjects had fatigue, palpitations, oligomenorrhea, polymenorrhea. Prolactin had positive correlation with TSH in hypothyroid subjects, their LH, FSH levels were normal and sex steroid levels were low. In contrary, majority of the hyperthyroid subjects had normal prolactin and FSH, high LH and high sex steroid levels. Conclusions: The study demonstrated that thyroid disease in women causes menstrual abnormalities due to altered gonadotropin patterns which in turn alter ovarian hormone pattern. Hypothyroidism is associated with hyperprolactinemia leading to anovulation and abnormal menstrual cycle. Hyperthyroidism is associated with increased levels of LH, estrogen and testosterone with normal levels of PRL and FSH. Screening, identifying and correcting thyroid disease should be undertaken to prevent infertility as early as possible.